2017
DOI: 10.15414/jmbfs.2017.7.1.67-74
|View full text |Cite
|
Sign up to set email alerts
|

AGROBACTERIUM-MEDIATED TRANSFORMATION OF TOMATO (LYCOPERSICON ESCULENTUM Mill.) USING A SYNTHETIC Cry1Ab GENE FOR ENHANCED RESISTANCE AGAINST TUTA ABSOLUTA (Meyrick)

Abstract: The effect of different plant hormones on in vitro regeneration of tomato (Lycopersicon esculentum Mill.) two cultivars Castle Rock and Super strain B, obtained from hypocotyls and cotyledons of cultured in vitro seedlings was examined. The optimal concentrations of plant growth regulators were the MS medium containing 3 mg L-1 of zeatin and 0.1 mg L-1 of NAA of cotyledon and hypocotyl explants of Super strain B cultivar. While, the best regeneration medium was the MS medium containing 1 mg L-1 ZEA, 0.5 mg L-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Transgenic cotton and brinjal cultivars having resistance to borers were permitted for commercial usage in Bangladesh and in Latin America, insect-resistant Bt soybean expressing cry1Ac + cry1Ab were allowed for production during 2014 ( Koch et al, 2015 ). Another study found that a synthetic cry1Ab gene introduced into tomato conferred resistance to the tomato leaf miner, T. absoluta , with 100 percent insect mortality at T 0 generation within 4–5 days ( Soliman et al, 2021 ). Rice lines (var.…”
Section: Biotechnological Approaches In Insect Pest Managementmentioning
confidence: 99%
“…Transgenic cotton and brinjal cultivars having resistance to borers were permitted for commercial usage in Bangladesh and in Latin America, insect-resistant Bt soybean expressing cry1Ac + cry1Ab were allowed for production during 2014 ( Koch et al, 2015 ). Another study found that a synthetic cry1Ab gene introduced into tomato conferred resistance to the tomato leaf miner, T. absoluta , with 100 percent insect mortality at T 0 generation within 4–5 days ( Soliman et al, 2021 ). Rice lines (var.…”
Section: Biotechnological Approaches In Insect Pest Managementmentioning
confidence: 99%
“…In constructing plant expression vector pBI121-cry1Ab, the coding sequence of synthetic cry1Ab was fused to CaMV35S promoter and the polyadenylation signal of the octopine synthase gene as described by Soliman et al (2017). The combination of 35S promoter and the castor bean catalase-1 intron has previously been demonstrated to confer high-level expression of foreign genes in transgenic plants (Tanaka et al, 1990).…”
Section: Insect Bioassaymentioning
confidence: 99%